150 years after the birth of Rosa Luxemburg: Actuality of her “Social Reform or Revolution” - Vera (Sociološki pregled, 2021)
The paper examines the actuality of Rosa Luxemburg’s Reform or revolution 150 years after her birth. The main method used is the content analysis of this important polemical pamphlet placed in the context of the time/space, i.e. when and where it was written, on the one hand, and today, on the other. The main finding is that Rosa’s work has remained relevant to our days since the capitalist mode of production is still characterized by internal contradictions producing barbaric consequences of exploitation and imperialist wars. These capitalist system’s consequences ensure the permanent actuality of the dilemma between socialism and barbarism confronted by Rosa Luxemburg throughout her life.